Difference in attack situational activity indicators between successful and less successful teams in elite men`s handball - Bajgoric, S.; Rogulj, N.; Cavala, M.; Burger, A. (Sport Sciences for Health, 2017)
Background: The most important characteristics of modern handball are the increase of speed and dynamics of attack and defence phase of the game. Aims: The aim of this work was to determine the differences in attack situational activity indicators between successful and less successful teams in elite men`s handball. Methods: Overall, 1848 matches of Croatian men`s premier league were analysed. The differences in attack situational activity indicators were determined using a set of 21 variables. Descriptive statistics were calculated for all examined variables of successful and less successful teams. The statistical difference significance in the attack situational activity indicators was tested using the t test analysis. Results: The results showed statistically significant difference between successful and less successful teams in the following variables: percentage of wing shot efficiency, percentage of 9 ms shot efficiency, average number of counter-attack shots, average number of goals from counter-attack, average number of half-counter-attack goals, average number of half-counter-attack goals, and average number of assistances. Results` analysis shows that these variables significantly determine the attack situational activity. Conclusions: In general, we can conclude that handball success was primarily determined by large number of fast attacks on the unorganised defence, as well as efficient realisation of attacks towards the set defence from the demanding situations on the wing and outer positions.